Oral physiology, sensory acuity, product experience and personality traits impact consumers' ability to detect particles in yoghurt. (March 2022) - Olarte Mantilla, Sandra M.; Shewan, Heather M.; Shingleton, Rebecca; Hort, Joanne; Stokes, Jason R.; Smyth, Heather E.
Highlights: Acceptance of particles in soft-foods is driven by both product and human factors. Higher fungiform papillae density relates with particle perception. Oral tactile sensitivity relates with particle perception. Abstract: Food texture is a major driver of consumer food acceptance and is influenced by the presence of particles. The objective of this study was to determine if individual differences in human factors (demographic, oral physiology, product experience and psychology) are associated to consumers' ability to detect particles in semisolid foods (namely yoghurt). A systematic design was employed involving nine yoghurt samples with spherical agar microgels added at levels in the range of human sensory threshold for particle detection in yoghurt. Consumers (n = 117) rated product acceptability, identified specific product sensory properties by Check All That Apply (CATA), and completed a questionnaire including demographics, personality typing, and product related questions. In addition, consumer saliva flow rate, mouth volume, tactile sensitivity, fungiform papillae density, and 6-n-propylthiouracil (PROP) and salt (NaCl) sensitivity were measured. Consumers who identified particles and/or drying in samples (by CATA) had significantly higher fungiform papillae density, were more oral tactile sensitive and were more sensitive to salt taste. The same consumers were more likely to have an open personality type, reported a preference for more cohesive yoghurt textures ( fatty, spoonable, not-separated ) and were more likely to have a history of consuming yoghurt products in combination with cereal and for preparation of smoothies. These results demonstrate that acceptance and rejection of particles in soft-foods is driven by a combination of intrinsic product factors and human factors. Understanding these drivers will assist the food industry to more accurately target products to specific markets.